LabOps: A flexible self-hosted workflow of open source tools for efficient collaboration within research laboratories. - Héctor D García-Verdugo; Cristian Román-Palacios (PLoS Computational Biology, 2025)
Effective collaboration, essential for success in academic environments, often requires efficient team communication and access to a team-oriented digital infrastructure. Despite the significance of efficient and effective collaboration within the academy, a standardized and structured suite for collaboration remains relatively overlooked. In the context of research labs, where multiple levels of collaboration often coexist, the ability to communicate and share resources in a timely and secure manner is critical. Modern research teams and institutions have historically attempted to solve these needs through proprietary, largely restrictive, and inflexible tools. Free and Open Source Software (FOSS) has facilitated the development of our modern computer-focused world by virtue of its legal, customizable, and accessible nature. However, FOSS remains weakly used for supporting communication, collaborative writing, storage, and other tasks within research labs. This paper discusses the implementation of a FOSS computational workflow for active collaboration within academic environments. We focus on identifying available tools that can support collaborative writing, instant messaging, data storage, among other tasks. The Lab Operations (LabOps) workflow presented in this paper-which can be self-hosted, adapted, and adopted at different levels-offers an alternative approach to off-the-shelf proprietary solutions for both within- and cross-lab communication. We discuss the benefits, flexibility, limitations, and potential approaches to adoption of the workflow.